Binding properties and structure–affinity relationships of food antioxidant butylated hydroxyanisole and its metabolites with lysozyme. (1st December 2015) - Wu, Di; Yan, Jin; Tang, Peixiao; Li, Shanshan; Xu, Kailin; Li, Hui
Highlights: BHA and its metabolites interact with lysozyme at different extents. Binding is predominantly the result of hydrogen bond and van der Waals force. Structural changes of lysozyme have been demonstrated. Computational studies of the test compounds with lysozyme substantiate the experimental findings. Abstract: Considering the harmful impact of food antioxidants on human bodies, thoroughly exposing their potential effects at the molecular level is important. In this study, the binding interactions of butylated hydroxyanisole (BHA), a phenolic antioxidant, and its different major metabolites tert -butylhydroquinone (TBHQ) and tert -butylbenzoquinone (TBQ) with lysozyme were examined via fluorescence, three-dimensional fluorescence, circular dichroism (CD), and ligand–protein docking studies. The three compounds caused strong quenching of lysozyme fluorescence by a static quenching mechanism but with different quenching efficiencies and different effects on the α-helix content of the lysozyme. The order of binding affinity of lysozyme for all test compounds is as follows: BHA > TBQ > TBHQ. Thermodynamic parameters indicated that hydrogen bonding and van der Waals forces perform dominant functions in the binding between these compounds and lysozyme. Furthermore, structure–affinity relationships between the model compounds and lysozyme were established on the basis of computational analyses.